Teachers’ Well-Being and Job Performance - Guiritan, Margorie O.; Sabacajan, Bazil T.; Nahial, Wenie L. (Future Science / FSH-PH Publications, 2025)
This study was conducted to determine teachers’ well-being and job performance in the new normal education due to COVID-19. Seventy-one teachers from the select schools in Mambajao District of DepEd-Camiguin were used as respondents of the study. A quantitative descriptive research design was used supplemented with a survey questionnaire as the main data-gathering tool. Research and health protocols as well as the ethical standards were observed in the implementation of the study. Appropriate statistical tools were used to analyze the data. Results showed that the majority of the respondents were females, in the middle-aged group, at least with units in master’s degree program, got the Teacher III position, and with at least 11 years of teaching experience. The respondents had a moderate extent of well-being and a very satisfactory job performance level. Despite the challenges of the learning modality, the well-being of the teachers did not influence their job performance. The demographics of the respondents did not influence difference in their well-being. This work showed that the respondents continued to perform their duties and functions amidst the challenges brought by the pandemic. Future researchers are encouraged to replicate this study by the time the health risks are controlled, and the learners go back to school for face-to-face class instruction.